Ileus Presenting with Malnutrition Associated with Anti-diarrheal Drugs in Pediatric Patient: A Case Report - Nidya Putri Ihsan; Irena Rosdiana (Archives of The Medicine and Case Reports, 2023)
Ileus is described as a complication after the use of regular anti-diarrheal agents, such as loperamide. In children, loperamide is not recommended as a regular treatment for acute diarrhea. This case report aimed to elaborate on the cases of Ileus as a side effect of anti-diarrheal drug use in children and to signify parents' education role in cases of malnutrition. In this study, a-7-year old boy came with symptoms of increasingly severe abdominal pain, distended abdomen, and difficulty defecating in the last 3 days after consumption of anti-diarrheal drugs by his parents within 6 months. The patient has a poor history of food consumption. Clinical investigations revealed anemia, leukocytosis, underweight, short stature, and local ileus. He was diagnosed with Ileus and malnutrition and treated with fluid therapy, antibiotics, and blood transfusion and was consulted by a pediatric surgeon. In conclusion, the use of anti-diarrheal agents should be avoided in connection with their safety for children and the complications that can arise. Parental knowledge plays an important role in preventing malnutrition in children.